Hypertension in Primary Open Angle Glaucoma - Suprada Pokharel; Dakki Sherpa; Om Krishna Malla (Journal of Nepal Medical Association, 2014)
Introduction: The impact of vascular factors in POAG is well known and controversial. Some reports have shown high blood pressure in POAG, some low systolic blood pressure and some described no difference in blood pressure between POAG and controls. However decreased ocular perfusion pressure was found in most of the studies. Our study aims to assess the role of hypertension in POAG .